Low-valent iron: an Fe(i) ate compound as a building block for a linear trinuclear Fe cluster1. Issue 73 (21st September 2015) - Lichtenberg, C.; Viciu, L.; Vogt, M.; Rodríguez-Lugo, R. E.; Adelhardt, M.; Sutter, J.; Khusniyarov, M. M.; Meyer, K.; de Bruin, B.; Bill, E.; Grützmacher, H.
<x xml:space="preserve">Abstract</x> A low-valent, linear, trinuclear iron cluster was synthesized from a new Fe(i) ate compound with a redox-active diazadiene-diolefin ligand and fully characterized.